Etanólise do óleo de coco: estudo das variáveis de processo - Almeida, Aldenyr Pontes de (2010)
Initially a comprehensive review on the production of biodiesel, as well as different types of catalysts used in the reactions and their respective routes, methyl or ethyl. Also during the review sought to demonstrate the cost effective use of biodiesel in conventional diesel grating, is the low emission of pollutants, is the simple fact is a renewable fuel, since the CO2 emitted during burning is absorbed again for oil seeds during all their lives, returning to produce more oils. Coconut oil had some advantages throughout the study, either by comparison of production between different oils, either because this has a culture that the intercropping system of planting. Leaving for the practice of biodiesel production, the initial step was the characterization of oil, by first determining the saponification number, where it was determined by the average molecular weight of used oil, then determined factors such as acid value, moisture and viscosity of the coconut oil used. After characterization, broke to the creation of 25 full factorial design with replicates, where due to operational problems reactions were carried 56 out of 64. Since the experiments were performed, it was possible to generate a graph comparing the experimental results obtained by the model and target as well as by analysis of variance proved the significance of the model. The analysis of response surfaces generated from the model served as a guide, directing where further work should follow ethanolysis with coconut oil. Finally, the study showed satisfactory results with approximately 100% yield and the determination of significant variables, which are the molar ratio and amount of catalyst as well as in obtaining a model that represents well the study process.